Japan: Decline of Doctoral Applicants—Crisis for Innovation? - Shimmi, Yukiko (International Higher Education, 2021)
For a number of reasons, while the number of doctoral graduates has been increasing in leading countries, in Japan the number of new entrants to doctoral programs has been decreasing. In order to bring innovation to society and industry, Japan needs to enhance the attractiveness of its doctoral programs with stable and long-term support.